Fabrication of Biodegraded Composite from Polypropylene, Polypropylene Grafted Maleic Anhydride, and Chempedak Seed (Artocarpus integer) Starch - Nasution, Darwin Yunus; Jumirah; Siregar, Amir Hamzah (Journal of Chemical Natural Resources, 2021)
Fabrication of biodegraded composite from polypropylene, polypropylene grafted maleic anhydride, and chempedak seed (Artocarpus integer) starch has been conducted. The stages were prepared starch of Cempedak seed, grafting process of maleic anhydride on polypropylene, and fabrication of composite with a composition ratio of PP: PP-g-MA: starch of chempedak seed (9.5:0.5:0.1)g, (9.5:0.5:0.2)g, (9.5:0.5:0.3)g, (9.5:0.5:0.4)g, (9.5:0.5:0.5) g, and PP: starch of chempedak seed (10:2)g. The composites obtained were characterized using tensile strength and elongation testing, surface morphology analysis by SEM, analysis in nature with the ability to decompose by biodegradable test, and functional groups analysis by FTIR spectroscopy. The results showed that the biodegradable composites have the best properties in the ratio of PP: PP-g-MA: starch of chempedak seed (9.5:0.5:0.1)g with the test results of tensile strength was 28.743 N/m2, and also the SEM results show that flat surface and improved homogeneity, and strong group interactions as well as having good biodegradable properties.